2014
DOI: 10.1104/pp.114.250928
|View full text |Cite
|
Sign up to set email alerts
|

PECTIN METHYLESTERASE48 Is Involved in Arabidopsis Pollen Grain Germination  

Abstract: Germination of pollen grains is a crucial step in plant reproduction. However, the molecular mechanisms involved remain unclear. We investigated the role of PECTIN METHYLESTERASE48 (PME48), an enzyme implicated in the remodeling of pectins in Arabidopsis (Arabidopsis thaliana) pollen. A combination of functional genomics, gene expression, in vivo and in vitro pollen germination, immunolabeling, and biochemical analyses was used on wild-type and Atpme48 mutant plants. We showed that AtPME48 is specifically expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 106 publications
(133 reference statements)
5
90
0
Order By: Relevance
“…6F). In agreement with published results on tobacco and Arabidopsis pollen tubes (Chebli et al, 2012;Leroux et al, 2015), the LM20-labeled esterified pectins were observed only at the tip of elongating pollen tubes and at the bud of germinating pollen, where they are secreted (Fig. 6G).…”
Section: Gfp-sec3a Tip Accumulation Is Correlated Inversely With the supporting
confidence: 80%
See 3 more Smart Citations
“…6F). In agreement with published results on tobacco and Arabidopsis pollen tubes (Chebli et al, 2012;Leroux et al, 2015), the LM20-labeled esterified pectins were observed only at the tip of elongating pollen tubes and at the bud of germinating pollen, where they are secreted (Fig. 6G).…”
Section: Gfp-sec3a Tip Accumulation Is Correlated Inversely With the supporting
confidence: 80%
“…The function of SEC3a in determining the site of the germination pore is in agreement with the earlier manifestation of the sec3a-1 mutant defect in pollen germination, as compared with other exocyst mutants. Similar to sec3a-1/GFP-SEC3a, pme48 mutant pollen developed multiple tips, indicating that pectin deesterification is required for the selection/maintenance of a single germinating tip (Leroux et al, 2015). In pme48, the LM20-labeled esterified pectins were more abundant and less focally localized (Leroux et al, 2015).…”
Section: Polar Localization Of Sec3a In Arabidopsis and Tobacco Pollementioning
confidence: 98%
See 2 more Smart Citations
“…Arabidopsis PME41 and PME48 participate in chilling/freezing tolerance through the regulation of brassinosteroid signaling and in pollen grain germination, respectively (Qu et al, 2011;Leroux et al, 2015). Arabidopsis PME3 has been found to interact directly with the cellulose-binding protein of the cyst nematode (Heterodera schachtii), reducing the level of pectin methylesterification in the cell wall to aid cyst nematode parasitism (Hewezi et al, 2008).…”
mentioning
confidence: 99%